Characteristics of digestate from methane fermentation as fertilizer and its utilization system - YOSHIHARA, Akane; KITAGAWA, Iwao; ORITATE, Fumiko; FUJITA, Mutsumi; NAKAMURA, Masato (Journal of the NARO Research and Development, 2025)
Methane fermentation is a technology used to produce biogas, a renewable energy source mostly containing methane, from organic matter such as livestock waste, food waste, and sludge through biological activity in an oxygen-free environment. The obtained biogas can be used as a fossil fuel alternative fuel for generators and boilers to generate electricity and heat, thereby contributing to reducing greenhouse gas (GHG) emissions. Additionally, the digestate can replace chemical fertilizers because they contain components such as nitrogen, phosphorus, and potassium. This paper summarizes the characteristics of digestate as a fertilizer and the current research trends.